2016
DOI: 10.1177/1687814016669472
|View full text |Cite
|
Sign up to set email alerts
|

Steady laminar flow in a 90° bend

Abstract: This research undertook an assessment of the characteristics of laminar flow in a 90°bend. The research utilised the computational fluid dynamics software tool ANSYS Fluent, adopting a finite volume method. The study focused on pressure decreases, velocity profiles, Dean vortices and Dean cells present in the bend. The results indicated that the Dean vortices first appear slightly at the bend, take a clear form at the exit pipe and disappear further downstream. This article contains also an original chart for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 15 publications
2
5
1
Order By: Relevance
“…At the mid-diastolic time point, the region downstream of the inlet on the inner curvature exhibited higher WSS than on the outer curvature. This corroborated past experimental findings that at low Reynolds numbers, high WSS were typically found at the inner curvature of flow in curved channels [ 20 ], and findings in previous simulations of embryonic hearts [ 17 , 21 ]. The reason for this was that under the highly laminar and viscous flow environment, flow directions are easily bent by adverse pressure gradient in a curved channel, resulting in velocities being higher at the inner curvature than at the outer curvature and causing higher shear stresses at the inner curvature.…”
Section: Resultssupporting
confidence: 92%
“…At the mid-diastolic time point, the region downstream of the inlet on the inner curvature exhibited higher WSS than on the outer curvature. This corroborated past experimental findings that at low Reynolds numbers, high WSS were typically found at the inner curvature of flow in curved channels [ 20 ], and findings in previous simulations of embryonic hearts [ 17 , 21 ]. The reason for this was that under the highly laminar and viscous flow environment, flow directions are easily bent by adverse pressure gradient in a curved channel, resulting in velocities being higher at the inner curvature than at the outer curvature and causing higher shear stresses at the inner curvature.…”
Section: Resultssupporting
confidence: 92%
“…Monophasic flows in curved pipes are parametrized with the pipe-to-curvature radii ratio δ = r R (r being the pipe radius and R the radius of curvature of the pipe) and the Reynolds number Re = 2U x r ν (U x being the mean flow velocity and ν the viscosity) and the secondary flow is generally parametrized thanks to the Dean number D = Re δ. Even if numerous studies have been devoted to classify the secondary flow with the Dean number, the decay length (minimum length to recover an axisymmetric flow after the curved part) has received less attention and the results mainly concern a Ubend [30][31][32][33]. Thus, to assess the proposed geometry for the CoSmo breadboard, both numerical simulations with OpenFOAM and PIV measurements have been performed to ensure that the flow at the entrance of the test section remains axisymmetric for the mass fluxes of interest G ≤ 150 kg.m −2 .s −1 that corresponds to Reynolds numbers Re ≤ 2063.…”
Section: Single-phase Flow Qualificationmentioning
confidence: 99%
“…Some of these studies include numerical simulations of the experiments using commercial fluid flow softwares such as ANSYS Fluent and OpenFOAM. A numerical assessment of the characteristics of laminar flow in a 90 • elbow was undertaken by van de Vosse et al [12] by adopting finite element methods and, more recently, by Pantokratoras [13] using ANSYS Fluent, who found that the velocity profiles at the bend inlet are shifted towards the inner pipe wall when the bend curvature is high, while they remain almost symmetric at low curvature. In addition, at high curvature and Reynolds numbers, the velocity profiles are shifted towards the outer pipe wall at the bend outlet and towards the inner wall at low Reynolds numbers, while when the curvature is low the velocity profiles are shifted towards the outer wall at the bend exit independently of the Reynolds number.…”
Section: Introductionmentioning
confidence: 99%